2016
DOI: 10.5194/acp-16-843-2016
|View full text |Cite
|
Sign up to set email alerts
|

The impact of atmospheric mineral aerosol deposition on the albedo of snow & sea ice: are snow and sea ice optical properties more important than mineral aerosol optical properties?

Abstract: Abstract. Knowledge of the albedo of polar regions is crucial for understanding a range of climatic processes that have an impact on a global scale. Light-absorbing impurities in atmospheric aerosols deposited on snow and sea ice by aeolian transport absorb solar radiation, reducing albedo. Here, the effects of five mineral aerosol deposits reducing the albedo of polar snow and sea ice are considered. Calculations employing a coupled atmospheric and snow/sea ice radiativetransfer model (TUV-snow) show that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(58 citation statements)
references
References 101 publications
(159 reference statements)
3
54
1
Order By: Relevance
“…Two modeling approaches were adopted. In the first scenario, the snow was consecutively given the optical properties of three snow types previously characterized by the authors (Lamare et al, 2016;Marks & King, 2014): cold polar snow, coastal windpacked snow and melting snow. A 1m thick cover of snow, representing the average thickness of the snowpack at station 1C, was defined on a 1 m thick sea ice.…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Two modeling approaches were adopted. In the first scenario, the snow was consecutively given the optical properties of three snow types previously characterized by the authors (Lamare et al, 2016;Marks & King, 2014): cold polar snow, coastal windpacked snow and melting snow. A 1m thick cover of snow, representing the average thickness of the snowpack at station 1C, was defined on a 1 m thick sea ice.…”
Section: Modelingmentioning
confidence: 99%
“…On sea ice, temperature gradients within the snowpack typically create a vapor pressure gradient from the relatively warm bottom upward to the colder layers in connect with the atmosphere. Such vapor gradients lead to an increase in snow grain size and a decrease in the optical scattering cross section of the snow, again leading to a decrease in light attenuation (Lamare et al, 2016;Libois et al, 2013). It has been suggested that 40 cm of snow cover is enough to prevent algal growth Mundy et al, 2007).Until recently, it has been anticipated that below such snow covers, little biological activity was occurring due to the absence of light.…”
Section: Introductionmentioning
confidence: 99%
“…The particles of sediments from the atmosphere, which could be both longdistance-transferred (as with Sahara dust) or local (pollution from industrial centers), can affect the sea ice albedo drastically (see e.g., Light et al, 1998;Marks and King, 2014;Lamare et al, 2016). For example, clay, slit, and sand particles are found in the ice situated far from a coastline in the Beaufort Sea (Reimnitz et al, 1993) and in the central Arctic (Nürnberg et al, 1994).…”
Section: Absorptionmentioning
confidence: 99%
“…Ideally, the absorption should be zero for undoped ice (no impurities). Absorption cross sections of Saharan dust from Lamare et al (2016) and chlorophyll in algae from Bricaud et al (2004) and Mundy et al (2011) are shown in Fig. 9 for comparison to the sea ice impurity absorption cross section.…”
Section: Derived Absorption and Scattering Cross Sections From Experimentioning
confidence: 99%
“…King et al, 2005;France et al, 2011Reay et al, 2012) and has also been adapted for use with sea ice (e.g. King et al, 2005;King, 2013, 2014;Lamare et al, 2016). The model has previously been experimentally validated for photochemistry in snow by Phillips and Simpson (2005), but it has not been experimentally validated for sea ice.…”
Section: Introductionmentioning
confidence: 99%